Deceptive Conducts before the Patent Office Challenges for Patent Law and Competition Law - Hoss, Eugenio (Munich Intellectual Property Law Center - MIPLC, 2019)
In an increasingly harmonized global patent landscape, few issues still distinguish the US patent system as much as its strict-and often criticized-duty of candor and its inequitable conduct doctrine. The EPO and most other countries around the world impose less burdensome disclosure duties upon patent applicants. What is there to learn from the experience in the US? Have these tools resulted in any benefit worth considering? Yet regardless of the disclosure duties imposed upon patent applicants, a deceptive conduct before the Patent Office could lead to unwarranted exclusive rights and have a negative impact on competition. Should antitrust law intervene? Is it a case of sham litigation? This work attempts to answer those questions through a comparative analysis, examining the law and case law in the US and in the EU from both a patent and a competition law perspective and seeking a workable theory of harm.